Making It Sound - The Performative Qatal and Its Explanation - Alexander Andrason (Journal of Hebrew Scriptures, 2012)
The Biblical Hebrew (henceforth, BH) suffix conjugation qatal— besides other meanings and functions1—is occasionally employed in order to perform acts (1.a) rather than to describe a situation or an activity (1.b). This means that, if determined conventional cir- cumstances are respected, the fact of uttering a given proposition with the verb in the qatal triggers a new state in the speaker’s reality. This is what scholars have been referring to as the ‘performative qatal,’ a use of the suffix conjugation where it appears2 with a clear performative force. This particular sense or function of the BH gram3 constitutes the object of the present paper.